Organic food product purchase behaviour: a pilot study for urban consumers in the South of Italy - Gracia, A.; de Magistris, T. (Spanish Journal of Agricultural Research, 2007)
The aim of this paper is to explain factors that influence organic food purchases of urban consumers in the South of Italy. To achieve this goal, a multivariate limited dependent variable model has been specified to simultaneously analyse consumers’ organic food purchases, the intention to purchase organic food products and the level of organic knowledge. This study uses survey data gathered from 200 consumers in Naples in 2003. Results indicate that consumers who are more willing to buy organic food products are more likely to buy a larger amount of those products. The intention to purchase depends on attitudes and organic product knowledge. Moreover, consumers’ attitudes towards health and environmental benefits provided by organic foods are the most important factors explaining, both, the intention to purchase and the final decision. Finally, income and organic knowledge positively influences the final decision to buy organic food products